Impact of the use of educacional audiovisual media on the academic performance of nursing students - Arriola Prieto, César Teodoro (2020)
Educational audiovisual media seek to facilitate dialogue, expression and participation of the main actors in the university classroom, both teachers and students, in the adoption of new practices that favor the development of classes. The objective of this study was to evaluate the impact of the use of educational audiovisual media on the academic performance of nursing students at a private university in Metropolitan Lima. The research focus is quantitative and the design corresponds to the descriptive correlational one. A sample of 123 nursing students of both sexes (112 women and 11 men) was considered. For data collection, a questionnaire was administered and a weighted averages record card was used; and for statistical processing, frequencies and percentages were used, as well as the normality test and the correlation inferential test. The results indicate that the use of educational audiovisual media correlates significantly with academic performance. Likewise, it was obtained that each one of the dimensions of the use of educational audiovisual media correlates significantly with the academic performance of the students in the sample. It was concluded that the use of educational audiovisual media has a positive impact on the academic performance of the nursing students evaluated. This study contributes to rethink the teacher's action regarding the optimal use of educational audiovisual media in the classroom to achieve the improvement of the student's academic performance in the learning processes.